2009
DOI: 10.1007/s12274-009-9098-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antibacterial activity of bifunctional Fe3O4-Ag core-shell nanostructures

Abstract: We describe a simple one-pot thermal decomposition method for the production of a stable colloidal suspension of narrowly dispersed superparamagnetic Fe 3 O 4 -Ag core-shell nanostructures. These biocompatible nanostructures are highly toxic to microorganisms. Antimicrobial activity studies were carried out on both Gram negative (Escherichia coli and Proteus vulgaris) and Gram positive (Bacillus megaterium and Staphylococcus aureus) bacterial strains. Efforts have been made to understand the underlying molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 28 publications
2
93
2
1
Order By: Relevance
“…This is potentially interesting since studies by Chudasama et al on core-shell silver nanostructures [33] and Nomiya et al on gold (I) complexes [21] also revealed that gold complexes are considerably more effective on Gram negative rather than Gram positive bacteria. However, further investigations are suggested to be carried out on other Gram positive and Gram negative strains to see whether the structure of cell wall in bacteria affects the enhancing effect of gold materials.…”
Section: +mentioning
confidence: 95%
“…This is potentially interesting since studies by Chudasama et al on core-shell silver nanostructures [33] and Nomiya et al on gold (I) complexes [21] also revealed that gold complexes are considerably more effective on Gram negative rather than Gram positive bacteria. However, further investigations are suggested to be carried out on other Gram positive and Gram negative strains to see whether the structure of cell wall in bacteria affects the enhancing effect of gold materials.…”
Section: +mentioning
confidence: 95%
“…Because of their size, AgNPs can easily reach the nuclear content of bacteria and they show a large and impressive surface area, where contact with bacteria is the greatest. 74,75 This could be the reason why these nanoparticles have the best antibacterial effect. For solid support systems, some researchers argue that Ag + ions released from the surface of AgNPs are responsible for their antibacterial activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Because of their size, Ag NPs can easily reach the nuclear content of bacteria and they present a large and impressive surface area, enabling broad contact with bacteria. 48,49 This could be the reason why they give the best antibacterial effect. For solid support systems, some researchers have argued that Ag + ions released from the surface of Ag NPs are responsible for their antibacterial activity.…”
Section: Antibacterial Activitymentioning
confidence: 99%